.NET framework essentials - Thai, Thuan L. (O'Reilly, 2003)
Fully updated for version 1.1 of the .NET Framework, .NET Framework Essentials, 3rd Edition is an objective, concise, no-nonsense overview of the Microsoft .NET Framework for developing web applications and services. Written for intermediate to advanced VB, C/C++, Java, and Delphi developers, .NET Framework Essentials, 3rd Edition is also useful to system architects and leaders who are assessing tools for future projects. .NET Framework Essentials touches all the bases--from the Common Language Run-Time (CLR) and key class libraries to the specialized packages for ASP.NET, Windows Forms, XML Web Services, and data access (ADO.NET). The authors survey each major .NET language, including VB.NET, C#, J#, and Managed C++, as well as MSIL, clearing away the noise and hype, and presenting a clear, practical look at the underlying technologies. .NET Framework Essentials also provides a handy reference to the most commonly used features of .NET Framework. Written by two veteran web applications developers, .NET Framework Essentials, 3rd Edition is one of the most complete, concise, and ultimately useful books to describe the breadth of technology represented by .NET. Compact and free of fluff or proprietary hype, .NET Framework Essentials is an outstanding value for experienced programmers and architects who need to get up to speed quickly.